Spectral Stowaways: Elizabeth Stuart Phelps's' Kentucky's Ghost' (1868). Issue 2 (1st November 2017) - Baker, Jen
Abstract : Elizabeth Stuart Phelps's Gothic short story 'Kentucky's Ghost' (1868) is amongst the most distinctive of ghost-child narratives to be published in the nineteenth and early twentieth centuries. This is owing, foremost, to its unique topographical and social setting; taking place at sea amongst an all-male crew of mostly lower-class sailors, rather than in the large suburban or rural house of middle or upper-class families that were typical of this Anglo-American literary sub-genre. This article considers the child-figure in Phelps's tale within intersecting frameworks: firstly, within a tradition of nautical folklore that is integral to producing the tale's Gothic tone. Secondly, within a contemporary context of frequently romanticised depictions of child-stowaways in literature, but a reality in which they were subjected to horrific abuse. Finally, her tale is discussed as a reformist piece that, despite its singularities, draws on darker versions of literary and folkloric dead-child traditions to produce a terrifying tale of retribution.